Impact of Social Responsibility on Income Tax: Empirical Evidence from Nigeria - Oyasor, Emmanuel Imuede (Ilomata International Journal of Tax and Accounting, 2024)
Introduction: the study investigated the relationship between community responsibility and effective income tax rate of listed insurers in Nigeria; determined the relationship between environmental responsibility and effective income tax rate of listed Insurers in Nigeria; examined the relationship between ethical responsibility and effective income tax rate of listed insurers in Nigeria; examined the relationship between firms’ diversity and effective income tax rate of listed insurers in Nigeria Method: The ex-post facto research design was employed and on published sourced from the Audited Annual Reports of the Listed Insurers between the periods of 2013-2022. The data were pre-tested using descriptive statistics, stationarity (unit) root test, Johansen co-integration. The hypotheses were analyzed using fixed effect (panel data). Result: The findings revealed that (p=0.8909>0.05) which indicated that there is no enough evidence to reject the null hypothesis one. Thus, community responsibility has no significant relationship with effective income tax rate of listed insurers in Nigeria. Similarly, the environmental responsibility indicated (p=0.4889>0.05) on effective income tax rate, which implied that environmental responsibility has no significant relationship with effective income tax rate of listed insurers in Nigeria. Ethical responsibility depicted (P=0.4801>0.05) on effective income tax rate, which implied that the ethical responsibility has no significant relationship with effective income tax rate of listed insurers in Nigeria. And Firms’ diversity showed (p = 0.7930 < 0.05) effective income tax rate, which revealed that the firms’ diversity has no significant relationship with effective income tax rate of listed insurers. Conclusion: The study concluded that community responsibility, environmental responsibility, ethical responsibility and firms’ diversity have no connection with corporate income tax of the listed insurance companies.